ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATERI BANGUN RUANG BERDASARKAN KRITERIA WATSON DITINJAU DARI PERBEDAAN GENDER SISWA SMP KELAS VIII - Muhammad Syahreza Fahlevi; Luvy Sylviana Zanthy (IKIP Siliwangi, 2021)
The purpose of this study was to analyze errors by male and female students based on Watson's criteria in solving the material on flat side spaces. From the results, it can be seen the types of student errors, percentages, and causes of student errors that occur. The design of this research is descriptive qualitative. Data collection is done by tests and interviews. Students are given a test to find out the type of error that occurs when they solve a problem. Interviews with subjects were conducted to find out the cause of their type of error in problem solving. In this study there were 10 subjects of grade VIII-1 students of SMPN 1 Cihampelas. Five male and female students. Data analysis was carried out by calculating the presentation of each indicator then interpreted based on Watson's criteria to determine the description of students' mistakes in working on questions and the factors that influenced students to make mistakes. Based on the results of this study, male students tend to make missing conclusions and incorrect procedures, the percentage obtained at the missing conclusions is 30% and the percentage of procedures that is not right is 23.3%. While female students tend to do missing data and incorrect data, the percentage obtained in the missing data is 23.3% and the percentage on the incorrect data is 20%.